Dabigatran can cause eosinophilic pleural and pericardial effusion with blood eosinophilia. (8th August 2016) - Voulgaris, Thanasis; Anevlavis, Stavros; Karpathiou, Georgia; Forest, Fabien; Koulelidis, Andreas; Froudarakis, Marios
Abstract: Eosinophilic pleural effusions (EPE) account for 5%–8% of all exudative pleural effusions. A pleural effusion is defined as eosinophilic if it contains 10% or more eosinophils. We present the case of a 70‐year‐old man with EPE, blood eosinophilia and pericardial effusion due to dabigatran, a novel anti‐thrombin agent.